The Use of Guide Services By Young People In The Era of The Development of Modern Technologies In The Opinion of Young People From High Schools In The Tri-City Agglomeration (Gdańsk, Sopot, Gdynia) - Marzena WANAGOS (Communications of International Proceedings, 2022)
In connection with the development of modern information and communication technologies, the question arises of the importance of the services of a traditional tourist guide today. The internet is available to the public and it is possible to use laptops, smartphones and tablets. More and more systems of spatial information, mobile guides and audiobguides are used. More and more tourist information is available on the websites of regions, towns or specific attractions. Many places can be visited in an interactive way. This article aims to show young people's views on using traditional tourist guide services. The main research problems discussed in this study focused on whether young people, despite the digital reality surrounding them and the availability of Internet information, value traditional guide services. Do they use these services and would they like to use them in the future? The study was conducted using a diagnostic survey in the form of a direct questionnaire. 224 people aged 17-19 were examined. Based on the study, it can be clearly stated that in the studied group, guide services are not losing popularity, students highly appreciate the qualifications of guides based on their experiences. And most importantly, they will be eager to use their services in the future.
Keywords: guide services; young people; modern technologies